Ichthyoarchaeology in the Americas: An introduction - Béarez, Philippe (2016)
Ichthyoarchaeology is a vital discipline for understanding human adaptation to the aquatic environments of the past; consequently, research in this area has been essential to address critical questions in the archaeology of the Americas. In many influential works in anthropological archaeology (Murdock, 1969; Kelly, 1995; Binford, 2001), fishing, which occurs across a huge diversity of environments and stems from both a natural and social context, basically encompasses foraging activities in aquatic environments. However, this ignores the technological abilities, seascape knowledge and socio-political organization that fishing requires; and the challenges and affordances that significantly differ in the hunting of mammals and birds in aquatic ecosystems. For example, fishing gear must be adapted to different aquatic conditions and to different fish taxa; this technology cannot be directly transferred from seal or seabird hunting devices. The acquisition of seascape knowledge is also a distinct factor: the intertidal zone is less dangerous than offshore areas, where humans can only enter with the support of artificial devices of mobility (e.g. canoes,watercrafts) and with acute knowledge regarding weather and sea conditions. Waterscape knowledge is also vital for predicting fish harvests and the seasonal organization of fishing.